The Phonology of Geminates in Bedouin Hijazi Arabic: An Optimality Theoretic Approach - AL SOLAMI, Majed (International Journal of Language and Literary Studies, 2022)
This paper examines the phonology of geminates in Bani Sulaim dialect, BSD, a Bedouin Hijazi dialect spoken in Saudi Arabia, within Optimality Theory framework, OT. The analysis covers lexical geminates, phonologically derived geminates through assimilation, and gemination as a compensatory strategy to compensate for lost mora after vowel deletion. The paper explores the interaction between vowel deletion, assimilation, and compensatory lengthening. In BSD, lexical geminates are phonemically contrastive with singletons in word medial and word final positions, while phonologically derived geminates are found in word initial and word final positions through assimilation. Using OT constraints, ranking the markedness constraints, that disallow certain consonant clusters in the output, higher than the faithfulness constraints shows that phonotactically prohibited consonant clusters are avoided through total assimilation that results in gemination. The final phonological process that generates geminates in BSD is a form of consonant lengthening to adhere to the moraic weight requirement of the dialect. In addition to presenting new data, this paper contributes to the sparse literature on geminates in Bedouin dialects.